(untitled) (Global Journal of Human-Social Science, 2018)
The students from different places with a mixture of their capacities may arise with a plenty of difficulties in a large class due to a large number of students and a great variety of attitudes of the students Although there is no alternative to delivering a traditional lecture to the students a modern view of teaching with a combination of team learning and use of modern technology is often more effective for the students Ensuring quality teaching at tertiary level in a large class poses unique challenges and difficulties because here a teacher has to undergo perplexities about student-diversity evaluation system contextual attention befitting student-centered regulation In this article several possible ways have been discussed to get over any challenge or risk for the management of a large class Moreover here the efficacy of modern techniques for the management of a large class has been envisaged for the improvement of students of tertiary level